Optimised power harvesting by controlling the pressure applied to molecular junctions. Issue 14 (4th March 2021) - Wang, Xintai; Ismael, Ali; Almutlg, Ahmad; Alshammari, Majed; Al-Jobory, Alaa; Alshehab, Abdullah; Bennett, Troy L. R.; Wilkinson, Luke A.; Cohen, Lesley F.; Long, Nicholas J.; Robinson, Benjamin J.; Lambert, Colin
Abstract : A major potential advantage of creating thermoelectric devices using self-assembled molecular layers is their mechanical flexibility. Abstract : A major potential advantage of creating thermoelectric devices using self-assembled molecular layers is their mechanical flexibility. Previous reports have discussed the advantage of this flexibility from the perspective of facile skin attachment and the ability to avoid mechanical deformation. In this work, we demonstrate that the thermoelectric properties of such molecular devices can be controlled by taking advantage of their mechanical flexibility. The thermoelectric properties of self-assembled monolayers (SAMs) fabricated from thiol terminated molecules were measured with a modified AFM system, and the conformation of the SAMs was controlled by regulating the loading force between the organic thin film and the probe, which changes the tilt angle at the metal-molecule interface. We tracked the thermopower shift vs. the tilt angle of the SAM and showed that changes in both the electrical conductivity and Seebeck coefficient combine to optimize the power factor at a specific angle. This optimization of thermoelectric performance via applied pressure is confirmed through the use of theoretical calculations and is expected to be a general method for optimising the power factor of SAMs.